C−H Bond Activation Relay (CHAR) of Proline Ester Derivatives Promoted by In Situ Triarylamine Radical Cation: Selective Synthesis of 4‐Bromopyrrole Derivatives. Issue 22 (14th March 2023) - Ding, Han; Zhang, Shuwei; Sun, Zheng; Ma, Qiyuan; Li, Yuemei; Yuan, Yu; Jia, Xiaodong
Abstract: Using the in situ generated triarylamine radical cation as an initiator, the sp 3 C−H bond of proline esters was smoothly oxidized and brominated through C−H activation relay (CHAR), giving a series of 4‐bromopyrroles in good yields with high regioselectivity. The mechanistic study revealed that the oxidation of the active C−H bond initiated the followed 1, 5‐HAT and bromination, which provides a new method to realize the functionalization of the remote C−H bond. Abstract : A C−H activation relay (CHAR) of proline esters was realized by the in situ generated tris(4‐bromophenyl)amine radical cation, selectively constructing the skeleton of 4‐bromopyrrole under mild reaction conditions.